Optimalisasi Peran Auditor Internal dalam Pencegahan Kecurangan: Budaya Lokal sebagai Variabel Moderasi - Usman Usman (Society, 2024)
This study investigates the effect of optimizing the role of internal auditors on fraud prevention by considering local culture as a moderating variable. This study aims to analyze the effect of optimizing the role of internal auditors on fraud prevention with local culture as a moderating variable. Sampling using purposive sampling, this study involved 87 auditors from the regional Inspectorate, with data collection through questionnaires analyzed using the PLS-SEM method and SmartPLS software version 4. The results of the study indicate that the role of internal auditors has a significant impact on fraud prevention, and the interaction between local culture and the role of internal audit has a significant influence on fraud prevention in local government. In general, the fraud prevention framework combines the dimensions of the role of internal auditors and local culture to create a system for preventing fraud and supporting the integrity and accountability of the organization. The analysis shows the R-Square value for the fraud prevention variable of 0.817, which indicates that the variables of the Role of Internal Audit and Local Culture have a significant influence on Fraud Prevention at 81.7%. These results indicate that the model has strong predictive power, and the rest has limitations in explaining 18.3% of the variance that can be explained by other variables that are not included in this research model.